Mikrodelece faktoru azoospermie jako jedna z prícin muzské infertility - Kolárová, J; Vrtĕl, R; Vodicka, R; Capková, P; Santavý, J (Casopis lekaru ceskych, 2003)
One of the possible causes of male infertility is microdeletion of the Y chromosome in the Yq11.23 region--named the azoospermia factor. These deletions are associated with azoospermia or severe oligozoospermia. In these cases, testicular histopathological findings comprise a wide spectrum, from total absence of germ cells, through arrest of their maturation to decreased sperm production. Most Y-chromosome microdeletions arise de novo but transmission from the father is also possible, either by the natural way or by assisted reproduction. In relation to the assisted reproduction, the relationship between the Y-deletions and presence of spermatozoa in testis, fertilization capability and embryo quality were examined. Heredity of the deleted Y chromosome is holandric and therefore all sons of males with deletions will carry the same defect and will probably have fertility problems. Another negative influence of deletions on a man's health has not yet been identified.
Keywords: Genetic Loci; mužské pohlaví; Seminal Plasma Proteins; Gene Deletion; genetické lokusy; Male; delece genu; lidé; Humans; mužská infertilita; Chromosomes, Human, Y; Infertility, Male; lidský chromozom Y; proteiny semenné plazmy